2007
DOI: 10.1007/s00125-007-0886-7
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms of alloxan- and streptozotocin-induced diabetes

Abstract: Alloxan and streptozotocin are toxic glucose analogues that preferentially accumulate in pancreatic beta cells via the GLUT2 glucose transporter. In the presence of intracellular thiols, especially glutathione, alloxan generates reactive oxygen species (ROS) in a cyclic redox reaction with its reduction product, dialuric acid. Autoxidation of dialuric acid generates superoxide radicals, hydrogen peroxide and, in a final iron-catalysed reaction step, hydroxyl radicals. These hydroxyl radicals are ultimately res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
1,266
3
150

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,836 publications
(1,567 citation statements)
references
References 92 publications
(116 reference statements)
57
1,266
3
150
Order By: Relevance
“…Moreover, STZ is potential to act as an intracellular nitric oxide (NO) donor and generates reactive oxygen species (ROS). The synergistic action of both NO and ROS may also contribute to DNA fragmentation and other deleterious changes caused by STZ [15] . In our study, elevated blood glucose level and decreased insulin level were observed in STZ-induced diabetic rats and it may be due to above stated mechanism of STZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, STZ is potential to act as an intracellular nitric oxide (NO) donor and generates reactive oxygen species (ROS). The synergistic action of both NO and ROS may also contribute to DNA fragmentation and other deleterious changes caused by STZ [15] . In our study, elevated blood glucose level and decreased insulin level were observed in STZ-induced diabetic rats and it may be due to above stated mechanism of STZ.…”
Section: Discussionmentioning
confidence: 99%
“…STZ utilizes low-affinity glucose transporter 2 in the plasma membrane and is selectively accumulated in pancreatic beta cells and also it damages other organs which can express this transporter, particularly kidney and liver [15] . In STZ-induced diabetic rats, elevated levels of SGPT and SGOT were observed and it may be due to STZ mediated liver damages which may cause leakage of above enzymes into the blood [20] .…”
Section: Discussionmentioning
confidence: 99%
“…STZ is a nitrosourea compound produced by Streptomyces achromogenes, which specifically induces DNA strand breakage in 毬 -cells causing diabetes mellitus [15][16][17][18] . This leads to insulin deficiency which in turn increases the blood sugar level.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all of these studies were conducted using experimental animals treated with diabetogenic drugs, such as STZ, that destroys the beta cell in the pancreas due to its alkylating properties and subsequently depletes the insulin secretion. 15 Therefore, STZ-induced DM is considered as a model of type 1 DM. By contrast, OLETF rats spontaneously develop hyperinsulinemia from 25-60 weeks of age and have been characterized as a genetic model of type 2 DM.…”
Section: Discussionmentioning
confidence: 99%